Kāvyaprakāśaḥ : Kavicandraviśvanāthakr̥tavivaraṇaṭīkopetaḥ - Mammaṭācārya (Nyū Bhāratīya Buka Kôrporeśana, 2002)
Classical treatise, with Kāvyaprakāśavivaraṇa Sanskrit commentary, on Sanskrit poetics.